Crystallographic texture and elemental composition mapped in bovine root dentin at the 200 nm level. Issue 2 (29th April 2013) - Deymier‐Black, A. C.; Veis, A.; Cai, Z.; Stock, S. R.
Summary The relationship between the mineralization of peritubular dentin (PTD) and intertubular dentin (ITD) is not well understood. Tubules are quite small, diameter ∼2 µm, and this makes the near‐tubule region of dentin difficult to study. Here, advanced characterization techniques are applied in a novel way to examine what organic or nanostructural signatures may indicate the end of ITD or the beginning of PTD mineralization. X‐ray fluorescence intensity (Ca, P, and Zn) and X‐ray diffraction patterns from carbonated apatite (cAp) were mapped around dentintubules at resolutions ten times smaller than the feature size (200 nm pixels), representing a 36% increase in resolution over earlier work. In the near tubule volumes of near‐pulp, root dentin, Zn intensity was higher than in ITD remote from the tubules. This increase in Zn2+, as determined by X‐ray absorption near edge structure analysis, may indicate the presence of metalloenzymes or transcription factors important to ITD or PTD mineralization. The profiles of the cAp 00.2 X‐ray diffraction rings were fitted with a pseudo‐Voigt function, and the spatial and azimuthal distribution of these rings' integrated intensities indicated that the cAp platelets were arranged with their c‐axes aligned tangential to the edge of the tubule lumen. This texture was continuous throughout the dentin indicating a lack of structural difference between in the Zn rich near‐tubular region and the remote ITD. SCANNING 36:231–240, 2014. © 2013 Wiley Periodicals, Inc.